Characterization of Near-Infrared Imaging and Indocyanine-Green Use Amongst General Surgeons: A Survey of 263 General Surgeons. (August 2022) - Verhoeff, Kevin; Mocanu, Valentin; Fang, Breanna; Dang, Jerry; Sun, Warren; Switzer, Noah J.; Birch, Daniel W.; Karmali, Shahzeer
Background: Near-infrared fluorescence imaging (NIRFI) is an increasingly utilized imaging modality, however its use amongst general surgeons and its barriers to adoption have not yet been characterized. Methods: This survey was sent to Canadian Association of General Surgeons and the Society of American Gastrointestinal and Endoscopic Surgeons members. Survey development occurred through consensus of NIRFI experienced surgeons. Results: Survey completion rate for those opening the email was 16.0% (n = 263). Most respondents had used NIRFI (n = 161, 61.2%). Training, higher volumes, and bariatric, thoracic, or foregut subspecialty were associated with use (P < .001). Common reasons for NIRFI included anastomotic assessment (n = 117, 72.7%), cholangiography (n = 106, 65.8%), macroscopic angiography (n = 66, 41.0%), and bowel viability assessment (n = 101, 62.7%). Technical knowledge, training and poor evidence were cited as common barriers to NIRFI adoption. Conclusions: NIRFI use is common with high case volume, bariatric, foregut, and thoracic surgery practices associated with adoption. Barriers to use appear to be lack of awareness, low confidence in current evidence, and inadequate training. High quality randomized studies evaluating NIRFI are needed to improve confidence in current evidence; if deemed beneficial, training will be imperative for NIRFI adoption.